Semiconductor electrolyte of mode-switchable photoelectrode device for producing H2O2 and generating power and application of semiconductor electrolyte
Nitrogen-doped carbon quantum dots prepared by betaine as a carbon source, as a p-n-type semiconductor electrolyte, solve the problems of low solar utilization and high cost in photoelectrocatalytic technology, and realize efficient H2O2 production and power generation under electric field, which promotes the Sustainable development of clean energy.
Patent Information
- Application Number
- CN202411435156.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-14
AI Technical Summary
The existing photoelectric catalytic technology has problems in the production of hydrogen peroxide (H2O2) and power generation, which have low solar utilization, complex equipment, high cost and efficient production of H2O2 under unbiased voltage, which limits its widespreadness in practical applications.
Nitrogen-doped carbon quantum dots (N-CQDs) are prepared by hydrothermal reaction using betaine as carbon source, and nitrogen source using ammonia, urea or pyridine as nitrogen sources. It is used as a p-n-type semiconductor electrolyte for photoelectricity of dual-photoelectrode devices without electric field Catalysis to achieve efficient production and power generation of H2O2.
It improves solar energy conversion efficiency, reduces production costs, achieves efficient H2O2 generation and continuous power generation under unbiased voltage, and promotes the sustainable development of clean energy.
Smart Images

Figure CN119307937A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of carbon quantum dot synthesis and electric field-free light radiation self-driven photoelectrochemical production of hydrogen peroxide and power generation, and specifically relates to a semiconductor electrolyte of a switchable mode photoelectrode device for producing H2O2 and generating electricity. Background Art
[0002] Energy issues are fundamental issues in the development of human civilization today. In the current energy structure, traditional fossil energy that emits pollutants and is non-renewable still occupies a major position. Finding new energy sources that are clean, renewable, have high energy density, and low cost is the key to the energy problem. Solar energy is an ideal primary energy source, and the key to its utilization lies in solar energy conversion technology. Hydrogen peroxide, as a green redox reagent and potential energy carrier, has a wide range of applications in the chemical industry, environmental remediation, green synthesis, fuel cell technology and other fields (Acc. Chem. Res. 2023, 56, 867-877.). The current industrial method for producing H2O2 is the anthraquinone method, that is, hydrogenation in an organic solvent and then countercurrent oxidation with air, purification, and concentration to obtain an aqueous solution of H2O2. This method is mature in technology and achieves a high degree of automation, but its production process is complex. Electrocatalysis can directly synthesize H2O2 in an aqueous solution, and the production process is relatively clean, but it consumes a lot of electricity, the cost is high, and it cannot be mass-produced. The advantages of photoelectrocatalysis (PEC) in preparing H2O2 are mild reaction conditions, green and sustainable, and the ability to prepare H2O2 with high performance, making it a promising solar energy conversion technology. At the same time, the performance of PEC can be improved from two aspects: photoelectrode materials and electrolyte solutions. More importantly, studies have shown that fine-tuning of the electrolyte is beneficial to the separation of photoelectrode charges and the efficiency of charge injection into the electrode, and sometimes even dominates the activity and selectivity of PEC, but there are few reports on research on electrolyte solutions.
[0003] Quantum dots are semiconductor nanomaterials with a diameter of 2 to 10 nm, with discrete energy level structures and unique photoelectric properties. Among them, carbon quantum dots (CQDs) are zero-dimensional nanomaterials with significant fluorescence properties. Their basic chemical structure consists of a carbon core composed of crystalline carbon and amorphous carbon, with hydroxyl (-OH), carboxyl (-COO - ), amino (-NH2) and quaternary ammonium (-N +(CH3)3) and other functional groups. These charged functional groups give CQDs good water solubility and unique energy band structure, making them a semiconductor electrolyte solution in the PEC system, matching the energy band of the photoelectrode and interacting with each other to improve the PEC performance. We found that different types of surface charges and different elements of CQDs play different roles. For example, an aqueous solution containing only CQDs with a negative surface charge is conducive to monofunctional PEC water oxidation (WOR) with an n-type semiconductor photoanode, while a solution containing CQDs with a positive surface charge can only enhance PEC oxygen reduction (ORR) when matched with a p-type photocathode. In addition, N-doped CQDs have higher conductivity, and pyridine-rich N can improve the selectivity of ORR two electrons. These have been confirmed. Therefore, N-doped pn-type CQDs (N-CQDs) have high research value as electrolytes for photoelectrocatalytic preparation of H2O2 (Appl. Catal., B, 2021, 296, 120378; J. Mater. Chem. A 2023, 11, 4162-4169; Chem. Eng. J. 2023, 477, 146903.).
[0004] Among the technologies for photoelectrocatalytic production of H2O2, PEC WOR and PEC ORR are dominant, but their solar energy utilization rate is low. Dual photoelectrode devices can increase the photovoltage and achieve bias-free operation. H2O2 can be produced in the dual chambers only by solar irradiation. In addition, fuel cells currently require packaging and being away from harsh conditions such as moisture, and there are very few devices that can generate electricity externally while ensuring high H2O2 production without bias. This has affected the conversion efficiency and H2O2 yield of solar power generation to a certain extent, limiting their wider application in actual production and life. Therefore, it is of great practical value to design and prepare more effective devices for self-driven H2O2 production and power generation without electric field light radiation. Summary of the invention
[0005] The purpose of the present invention is to provide a nitrogen-doped carbon quantum dot prepared with betaine as a carbon source and ammonia, urea or pyridine as a nitrogen source, which can be directly used as an electrolyte in a two-electrode system to achieve the dual efficiency of producing H2O2 and generating electricity without bias.
[0006] In view of the above-mentioned purpose, the semiconductor electrolyte of the switchable mode photoelectrode device provided by the present invention for producing H2O2 and generating electricity has a semiconductor property of pn type, and is nitrogen-doped carbon quantum dots obtained by hydrothermal reaction with betaine as a carbon source and ammonia, urea or pyridine as a nitrogen source.
[0007] The specific preparation method of the above-mentioned semiconductor electrolyte is: add betaine and a nitrogen source into deionized water, control the concentration of betaine in the deionized water to be 0.01-1 mol / L, transfer the betaine into a reactor after completely dissolving it by ultrasound, conduct hydrothermal reaction at 180-220°C for 5-12 hours, cool to room temperature, centrifuge, filter, dialyze, and freeze-dry to obtain nitrogen-doped carbon quantum dots.
[0008] The betaine is selected from any one of glycine betaine, lauryl betaine, butyryl betaine, 3-sulfopropyl dodecyl dimethylamine betaine, 3-sulfopropyl tetradecyl dimethylamine betaine, 3-sulfopropyl hexadecyl dimethylamine betaine, alanine betaine, aminopentanobetaine, valine betaine, 3-(decyldimethylammonium) propane-1-sulfonic acid inner salt, phenylalanine betaine, N,N,N-trimethyllysine hydrochloride, stachydrine, and trigonelline.
[0009] In the method for preparing the semiconductor electrolyte, the molar ratio of the nitrogen source to betaine is preferably 0.01 to 0.1:1.
[0010] The present invention provides an application of the semiconductor electrolyte to photocatalytically produce H2O2, and the specific method is: in a two-chamber photoelectrode device containing a proton exchange membrane, the photoanode is BiVO4, TiO2, WO3, ZnO, Co3O4, Bi2WO6, α-Fe2O3, etc., the photocathode is Cu2O, polyterthiophene, CdS, GaN, CuO, g-C3N4, perovskite oxide, etc., the electrolytes in the anode chamber and the cathode chamber are both aqueous solutions of the semiconductor electrolyte of the present invention, and then 390-780nm light radiation is used in the absence of an electric field, and H2O2 is produced in both chambers.
[0011] The present invention also provides the application of the above-mentioned semiconductor electrolyte in solar power generation. The specific method is: in a one-chamber photoelectrode device without a proton exchange membrane, the photoanode is BiVO4, TiO2, WO3, ZnO, Co3O4, Bi2WO6, α-Fe2O3, etc., the photocathode is Cu2O, polyterthiophene, CdS, GaN, CuO, g-C3N4, perovskite oxide, etc., the aqueous solution of the semiconductor electrolyte of the present invention is the electrolyte, the photoanode is connected to the positive electrode of an external circuit device (such as an LED lamp, a small fan, etc.), and the photocathode is connected to the negative electrode of the external circuit device, and 390-780nm light radiation is used to supply electric energy to the external circuit device.
[0012] In the above two applications, the photoanode and photocathode only need to have sufficient photovoltage, and the potential of oxidation / reduction to produce H2O2 is between the semiconductor energy bands, and are not limited to the above photoelectrodes.
[0013] In the above two applications, the pH range of the aqueous solution of the semiconductor electrolyte is 2 to 9, and the concentration is 5 to 200 mg / mL.
[0014] The beneficial effects of the present invention are as follows:
[0015] The present invention uses pn-type nitrogen-doped carbon quantum dots synthesized based on betaine as electrolytes to prepare a light-radiation self-driven dual photoelectrode device with switchable modes in the absence of an electric field to promote the generation of H2O2 and power generation. Betaine is used as a carbon source, and ammonia, urea or pyridine are used as nitrogen sources. A simple hydrothermal method is used to synthesize nitrogen-doped carbon quantum dots (N-CQDs). The raw material cost is low, the synthesis method is simple, and it is easy to promote. The prepared N-CQDs can be dispersed in an aqueous solution as an electrolyte for the photoanode chamber and the photocathode chamber of a two-chamber photoelectrode device. Compared with traditional electrolytes, the photoelectric system constructed by N-CQDs can not only achieve unbiased conditions, greatly improving the conversion efficiency of solar energy, but also has excellent activity and greatly improved the selectivity of producing H2O2. When the N-CQDs aqueous solution is placed as an electrolyte in a single-chamber photoelectrode device without a separation membrane, it can continuously supply power to the outside for hundreds of hours. Therefore, the present invention extends a conceptually new "semiconductor electrolyte" towards more practical dual-photoelectrode devices to harvest sustainable solar power generation and valuable chemicals production under a cleaner, efficient and low-cost route. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is the XRD pattern of glycine N-CQDs synthesized using glycine betaine as a precursor in Example 1.
[0017] Figure 2 This is the XRD pattern of lauryl N-CQDs synthesized using lauryl betaine as a precursor in Example 2.
[0018] Figure 3 This is the XRD pattern of butyryl N-CQDs synthesized using butyrylbetaine as a precursor in Example 3.
[0019] Figure 4 This is the Raman spectrum of butyryl N-CQDs synthesized using butyrylbetaine as a precursor in Example 3.
[0020] Figure 5 This is the XPS graph of C of butyryl N-CQDs synthesized using butyrylbetaine as a precursor in Example 3.
[0021] Figure 6 This is the XPS graph of N of butyryl N-CQDs synthesized using butyrylbetaine as a precursor in Example 3.
[0022] Figure 7This is the XPS graph of O of butyryl N-CQDs synthesized using butyrylbetaine as a precursor in Example 3.
[0023] Figure 8 3 is a structural diagram of butyryl N-CQDs synthesized using butyrylbetaine as a precursor in Example 3.
[0024] Fig. 9 It is the UV-visible absorption graph of the aqueous solution of N-CQDs synthesized using glycine betaine, lauryl betaine and butyryl betaine as precursors in Examples 1, 2 and 3, respectively.
[0025] Fig.10 1 is the fluorescence spectrum of the aqueous solution of glycine N-CQDs synthesized using glycine betaine as a precursor in Example 1.
[0026] Fig.11 This is the fluorescence spectrum of the aqueous solution of lauryl N-CQDs synthesized using lauryl betaine as a precursor in Example 2.
[0027] Fig.12 This is the fluorescence spectrum of the aqueous solution of butyryl N-CQDs synthesized using butyrylbetaine as a precursor in Example 3.
[0028] Fig.13 The WORLSV curve test graph is a graph of the N-CQDs aqueous solution synthesized with KHCO3 aqueous solution and glycine betaine, lauryl betaine and butyryl betaine as precursors in Examples 1, 2 and 3 respectively as the electrolyte under dark and light conditions.
[0029] Fig.14 It is a test graph of the ORRLSV curve under dark and light conditions using a citric acid-disodium hydrogen phosphate buffer and an aqueous solution of N-CQDs synthesized as precursors using glycine betaine, lauryl betaine and butyryl betaine in Examples 1, 2 and 3, respectively, as an electrolyte.
[0030] Fig.15 The WORLSV curve test graph is a graph of the WORLSV curves of the N-CQDs synthesized using KHCO3 aqueous solution and aqueous solutions of N-CQDs synthesized using 3-sulfopropyl dodecyldimethylamine betaine (dodecylsulfonate betaine), 3-sulfopropyl tetradecyldimethylamine betaine (tetradecylsulfonate betaine) and 3-sulfopropyl hexadecyldimethylamine betaine (hexadecylsulfonate betaine) as precursors as electrolytes under dark and light conditions.
[0031] Fig.16This is a test graph of the ORRLSV curve of the aqueous solution of N-CQDs synthesized using citric acid-disodium hydrogen phosphate buffer and 3-sulfopropyl dodecyldimethylamine betaine (dodecylsulfonate betaine), 3-sulfopropyl tetradecyldimethylamine betaine (tetradecylsulfonate betaine) and 3-sulfopropyl hexadecyldimethylamine betaine (hexadecylsulfonate betaine) as precursors as the electrolyte under dark and light conditions.
[0032] Fig.17 This is a Mott-Schottky curve test diagram of butyryl N-CQDs synthesized using butyrylbetaine as a precursor in Example 3.
[0033] Fig.18 This is an on-off LSV curve test graph of the aqueous solution of butyryl N-CQDs synthesized with butyrylbetaine as a precursor in Example 3 and the traditional electrolyte (the photoanode electrolyte is KHCO3 aqueous solution, and the photocathode electrolyte is citric acid-disodium hydrogen phosphate buffer) in devices of different modes under the conditions of alternating darkness and light for 5s.
[0034] Fig.19 It is a detection curve of the total H2O2 production within 1 hour without bias in the aqueous solution of butyryl N-CQDs synthesized with butyrylbetaine as a precursor in Example 3 and the traditional electrolyte (the photoanode electrolyte is KHCO3 aqueous solution, and the photocathode electrolyte is citric acid-disodium hydrogen phosphate buffer) in devices of different modes.
[0035] Fig. 20 This is a graph of the total Faraday efficiency (FE) detection curves of the aqueous solution of butyryl N-CQDs synthesized with butyrylbetaine as a precursor in Example 3 and the traditional electrolyte (the photoanode electrolyte is a KHCO3 aqueous solution, and the photocathode electrolyte is a citric acid-disodium hydrogen phosphate buffer) for H2O2 within 1 hour without bias in devices of different modes.
[0036] Fig.21 This is a JV curve test diagram of the aqueous solution of butyryl N-CQDs synthesized with butyrylbetaine as a precursor in Example 3 and the traditional electrolyte (the photoanode electrolyte is KHCO3, and the photocathode electrolyte is citric acid-disodium hydrogen phosphate buffer) in a one-chamber photoelectrode device filled with O2.
[0037] Fig. 22 This is a JV curve test diagram of the two-chamber photoelectrode device in air of an aqueous solution of butyryl N-CQDs synthesized using butyrylbetaine as a precursor in Example 3.
[0038] Fig.23This is a model diagram of a one-chamber photoelectrode device composed of an aqueous solution of butyryl N-CQDs synthesized using butyrylbetaine as a precursor in Example 3, which is used as a light intensity meter for indicating outdoor operations and a light sensor model diagram for indicating light intensity in a greenhouse. DETAILED DESCRIPTION
[0039] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited to these embodiments.
[0040] Example 1
[0041] 0.59 g (5 mmol) of glycine betaine was weighed into a beaker, and 5 mL of deionized water and 0.1 mL of 1 mol / L ammonia water were added to dissolve it. After ultrasonication for 20 min, the resulting solution was transferred to a polytetrafluoroethylene-lined reactor, and the reactor was sealed. The hydrothermal reaction was carried out at 220 ° C for 12 h. After the reaction, the reactor was cooled to room temperature, and the reaction solution was centrifuged at 10000 r / min for 10 min. The supernatant was filtered with a filter membrane with a pore size of 220 nm and a dialysis membrane with a pore size of 500 mesh, respectively. After freeze-drying, 0.12 g of light yellow solid glycine N-CQDs was obtained, which was dispersed in 2 mL of deionized water to prepare a glycine N-CQDs aqueous solution with a pH of 8.28 and a concentration of 60 mg / mL.
[0042] Example 2
[0043] Weigh 0.04 g (0.15 mmol) of lauryl betaine into a beaker, add 5 mL of deionized water and 0.1 mL of 1 mol / L ammonia water to dissolve it. After ultrasonication for 20 min, the resulting solution was transferred to a polytetrafluoroethylene-lined reactor, and the reactor was sealed. The hydrothermal reaction was carried out at 220 ° C for 12 h. After the reaction, the reactor was cooled to room temperature, and the reaction solution was centrifuged at 10000 r / min for 10 min. The supernatant was filtered with a filter membrane with a pore size of 220 nm and a dialysis membrane of 500 mesh, respectively. After freeze-drying, 12 mg of yellow solid lauryl N-CQDs was obtained, which was dispersed in 2 mL of deionized water to prepare a lauryl N-CQDs aqueous solution with a pH of 5.6 and a concentration of 6 mg / mL.
[0044] Example 3
[0045] Weigh 0.07 g (0.48 mmol) of butyrylbetaine into a beaker, add 5 mL of deionized water and 0.1 mL of 1 mol / L ammonia water to dissolve, and after ultrasonication for 20 min, transfer the resulting solution into a polytetrafluoroethylene-lined reactor, seal the reactor, and perform hydrothermal reaction at 180 ° C for 5 h. After the reaction, cool the reactor to room temperature, centrifuge the reaction solution at 10000 r / min for 10 min, and filter the supernatant with a filter membrane with a pore size of 220 nm and a dialysis membrane of 500 mesh, respectively. After freeze-drying, 18 mg of dark yellow solid butyryl N-CQDs was obtained, which was dispersed in 2 mL of deionized water to prepare a butyryl N-CQDs aqueous solution with a pH of 8.6 and a concentration of 9 mg / mL.
[0046] Example 4
[0047] 1.17 g (3.5 mmol) of dodecyl betaine was weighed into a beaker, and 5 mL of deionized water and 0.1 mL of 1 mol / L ammonia water were added to dissolve it. After ultrasonication for 20 min, the resulting solution was transferred to a polytetrafluoroethylene-lined reactor, and the reactor was sealed. The hydrothermal reaction was carried out at 220 ° C for 12 h. After the reaction, the reactor was cooled to room temperature, and the reaction solution was centrifuged at 10000 r / min for 10 min. The supernatant was filtered with a filter membrane with a pore size of 220 nm and a dialysis membrane of 500 mesh, respectively. After freeze-drying, 0.25 g of yellow solid dodecyl N-CQDs was obtained, which was dispersed in 2 mL of deionized water to prepare a dodecyl N-CQDs aqueous solution with a pH of 2.92 and a concentration of 125 mg / mL.
[0048] Example 5
[0049] Weigh 0.91 g (2.5 mmol) of tetradesulfonate betaine into a beaker, add 5 mL of deionized water and 0.1 mL of 1 mol / L ammonia water to dissolve, and after ultrasonic treatment for 20 min, transfer the resulting solution into a polytetrafluoroethylene-lined reactor, seal the reactor, and perform hydrothermal reaction at 220 ° C for 11 h. After the reaction, cool the reactor to room temperature, centrifuge the reaction solution at 10000 r / min for 10 min, and filter the supernatant with a filter membrane with a pore size of 220 nm and a dialysis membrane of 500 mesh, respectively. After freeze-drying, 0.2 g of yellow solid tetradesulfonate N-CQDs was obtained, which was dispersed in 2 mL of deionized water to prepare a tetradesulfonate N-CQDs aqueous solution with a pH of 3.05 and a concentration of 100 mg / mL.
[0050] Example 6
[0051] 1.37 g (3.5 mmol) of hexadecanesulfonate betaine was weighed into a beaker, and 5 mL of deionized water and 0.1 mL of 1 mol / L ammonia water were added to dissolve it. After ultrasonication for 20 min, the resulting solution was transferred to a polytetrafluoroethylene-lined reactor, and the reactor was sealed. The hydrothermal reaction was carried out at 220 ° C for 8 h. After the reaction, the reactor was cooled to room temperature, and the reaction solution was centrifuged at 10000 r / min for 10 min. The supernatant was filtered with a filter membrane with a pore size of 220 nm and a dialysis membrane of 500 mesh, respectively. After freeze-drying, 0.3 g of yellow solid hexadecanesulfonate N-CQDs was obtained, which was dispersed in 2 mL of deionized water to prepare a hexadecanesulfonate N-CQDs aqueous solution with a pH of 3.01 and a concentration of 150 mg / mL.
[0052] The N-CQDs powders obtained in Examples 1, 2, and 3 were characterized by X-ray powder diffractometer. Figures 1 to 3 , broad diffraction peaks appear at 2θ=23.4°, 23.9°, and 24.2°, respectively, indicating that N-CQDs have an amorphous graphite structure; laser confocal micro-Raman spectrometer was used to characterize Example 3, and the following results were obtained: Figure 4 The Raman spectrum shown in FIG. 1 can prove that butyryl N-CQDs are successfully doped with N in the graphite lattice; the butyryl N-CQDs obtained in Example 3 are characterized by XPS using an X-ray photoelectron spectrometer, and the results are as follows: Figures 5 to 7 The XPS spectra of the elements C, N, and O can be analyzed to obtain the valence states of the elements in the carbon dots. Figure 8 The specific structure of butyryl N-CQDs is shown.
[0053] The N-CQDs aqueous solution obtained in Examples 1, 2, and 3 was subjected to UV-visible light absorption and fluorescence tests. Figures 9 to 12 As can be seen from the figure, the N-CQDs aqueous solution has a peak starting from 500nm and has excitation wavelength dependence, indicating that carbon dots can be excited by visible light irradiation.
[0054] The N-CQDs aqueous solution obtained in Examples 1 to 6 was used as an electrolyte, and an electrochemical test was performed using an electrochemical workstation CHI660E. Ag / AgCl was used as a reference electrode, a Pt electrode was used as a counter electrode, and a 4 cm 2 FTO board covers 2cm 2 BiVO4 or Cu2O was used as the working electrode, and a three-electrode system was constructed and inserted into the electrolyte. With 450nm wavelength light as the light source, photoelectrochemical tests of WOR and ORR were performed (oxygen reduction tests required ventilation half an hour in advance). LSV tests were performed under dark and light conditions, and the results were as follows: Figures 13-16From the LSV graph, it can be seen that the photocurrent of the N-CQDs aqueous solution increases sharply under light conditions, indicating that the N-CQDs are excited under light to improve the water oxidation or oxygen reduction performance.
[0055] The butyryl N-CQDs obtained in Example 3 were scanned by an electrochemical workstation to scan the Mott-Schottky curve and characterize the energy level structure of the butyryl N-CQDs. The results are shown in Fig.17 , proving that butyryl N-CQDs have both p-type and n-type semiconductor characteristics.
[0056] The butyryl N-CQDs aqueous solution obtained in Example 3 was used as an electrolyte and compared with a conventional electrolyte (the photoanode electrolyte was a KHCO3 aqueous solution and the photocathode electrolyte was a citric acid-sodium hydrogen phosphate buffer solution). The electrochemical test was performed using an electrochemical workstation CHI660E at 10 cm 2 FTO board covers 6cm 2 BiVO4 or Cu2O was used as the working electrode, and a two-electrode system was constructed in a two-chamber photoelectrode device with a proton exchange membrane and a one-chamber photoelectrode device without a separation membrane, respectively, and inserted into the electrolyte. Photoelectrochemical tests were performed using 450nm wavelength light as the light source. On-off LSV tests were performed under no bias, dark and light alternating for 5s. The results are shown in Figure 1. Fig.18 This indicates that the photoelectrode device with butyryl N-CQDs aqueous solution as the electrolyte in the two-electrode system has a higher photocurrent than the traditional electrolyte, a higher photoelectric performance, and a single-chamber photoelectrode device has the highest activity. Under no bias, quantitative detection of H2O2 within 1 hour, the results are as follows Figures 19-20 , proving that the pn-type semiconductor electrolyte based on nitrogen-doped betaine carbon quantum dots can not only construct a dynamic pn junction with n-type BiVO4 photoanode and p-type Cu2O photocathode, but also serve as an active site for WOR and ORR, mainly producing H2O2, and its yield is significantly higher than that of a one-chamber photoelectrode device and a two-chamber photoelectrode device with a traditional electrolyte. The JV curve test is as follows Figures 21-22 , indicating that in the one-chamber photoelectrode device, butyryl N-CQDs mainly act as charge carriers to generate electrical energy; and we used the one-chamber photoelectrode device to build a scene model, and the results are as follows Fig.23 , proving that one-chamber photoelectrode devices have better development prospects in power generation than other solar cells and PEC cells due to the advantages of simple dual photoelectrodes and immunity to moisture.
[0057] In summary, the nitrogen-doped carbon quantum dots synthesized by the present invention using betaine as the carbon source and ammonia water as the nitrogen source have pn-type semiconductor characteristics, and form a switchable dual-functional dual-photoelectrode system with BiVO4 photoanode and Cu2O photocathode. Under no bias and 450nm illumination, on the one hand, they show high performance in producing H2O2 in the two-chamber photoelectrode device, and on the other hand, they show good power generation capacity in the one-chamber photoelectrode device. This simple switchable dual-photoelectrode device provides a new strategy for the self-driven production of H2O2 and power generation system without electric field light radiation, laying a certain foundation for further research in the future.
Claims
1. A semiconductor electrolyte for a switchable mode photoelectrode device for producing H2O2 and generating electricity, characterized in that: The semiconductor electrolyte has a pn-type semiconductor property, and is a nitrogen-doped carbon quantum dot obtained by hydrothermal reaction using betaine as a carbon source and ammonia, urea or pyridine as a nitrogen source; The betaine is selected from any one of glycine betaine, lauryl betaine, butyryl betaine, 3-sulfopropyl dodecyl dimethylamine betaine, 3-sulfopropyl tetradecyl dimethylamine betaine, 3-sulfopropyl hexadecyl dimethylamine betaine, alanine betaine, aminopentanobetaine, valine betaine, 3-(decyldimethylammonium) propane-1-sulfonic acid inner salt, phenylalanine betaine, N,N,N-trimethyllysine hydrochloride, stachydrine, and trigonelline.
2. The semiconductor electrolyte of the switchable mode photoelectrode device for producing H2O2 and generating electricity according to claim 1, characterized in that: Betaine and a nitrogen source are added into deionized water, the concentration of betaine in the deionized water is controlled to be 0.01-1 mol / L, the betaine is completely dissolved by ultrasound, and then transferred into a reactor, and hydrothermally reacted at 180-220° C. for 5-12 hours. After cooling to room temperature, the reaction is centrifuged, filtered, dialyzed, and freeze-dried to obtain nitrogen-doped carbon quantum dots.
3. The semiconductor electrolyte of the switchable mode photoelectrode device for producing H2O2 and generating electricity according to claim 2, characterized in that: The molar ratio of the nitrogen source to betaine is 0.01-0.1:
1.
4. Use of the semiconductor electrolyte according to claim 1 for photocatalytic production of H2O2.
5. The use of semiconductor electrolyte for photocatalytic production of H2O2 according to claim 4, characterized in that: In a two-chamber photoelectrode device containing a proton exchange membrane, any one of BiVO4, TiO2, WO3, ZnO, Co3O4, Bi2WO6, and α-Fe2O3 is used as a photoanode, and any one of Cu2O, polyterthiophene, CdS, GaN, CuO, g-C3N4, and perovskite oxide is used as a photocathode. The electrolytes in the anode chamber and the cathode chamber are both aqueous solutions of the semiconductor electrolyte described in claim 1. Then, light radiation of 390 to 780 nm is used in the absence of an electric field, and H2O2 is produced in both chambers.
6. The use of semiconductor electrolyte for photocatalytic production of H2O2 according to claim 5, characterized in that: The pH range of the aqueous solution of the semiconductor electrolyte is 2 to 9, and the concentration is 5 to 200 mg / mL.
7. Use of the semiconductor electrolyte according to claim 1 in solar power generation.
8. Use of the semiconductor electrolyte in solar power generation according to claim 7, characterized in that: In a one-chamber photoelectrode device without a proton exchange membrane, any one of BiVO4, TiO2, WO3, ZnO, Co3O4, Bi2WO6, and α-Fe2O3 is used as a photoanode, and any one of Cu2O, polyterthiophene, CdS, GaN, CuO, g-C3N4, and perovskite oxide is used as a photocathode. The aqueous solution of the semiconductor electrolyte described in claim 1 is used as an electrolyte. The photoanode is connected to the positive electrode of an external circuit device, and the photocathode is connected to the negative electrode of the external circuit device. Light radiation of 390 to 780 nm is used to supply electrical energy to the external circuit device.
9. Use of the semiconductor electrolyte in solar power generation according to claim 8, characterized in that: The pH range of the aqueous solution of the semiconductor electrolyte is 2 to 9, and the concentration is 5 to 200 mg / mL.
Citation Information
Cited By
G-C3N4-modified GaN nanorod photoelectrode material, photocathode, photoelectrochemical cell, and preparation method and application of g-C3N4-modified GaN nanorod photoelectrode material, photocathode and photoelectrochemical cell
CN120082921A